Moj Lwow - Wittlin, Jozef, 1896-1976. (Warszawa : Czytelnik, 1991)
A personal memoir of the author and of his city Lwow in former Poland.
Originally published: New York, Biblioteka Polska, 1946.
Keywords: Wittlin, Jozef, -- 1896- -- Homes and haunts -- Ukraine -- Lviv; Authors, Polish -- 20th century -- Biography; Lʹviv (Ukraine) -- Description and travel